FDG-Avid Tracheal Mass and Cartilage Involvements in ANCA-Negative Granulomatosis With Polyangiitis. (January 2022) - Tanaka, Hiroki; Hosono, Makoto; Kawabata, Kazuna; Kageyama, Goichi; Yamashita, Mai
Abstract : Abstract: A 57-year-old woman was referred for progressive dyspnea. CT showed a tracheal mass, suspicious of tracheal neoplasm. The lesion was partially resected, and nonspecific granulation tissue was observed on histology. Her symptoms and CT findings worsened. FDG PET/CT showed increased FDG accumulation in the nasal septum and left eustachian tube in addition to the tracheobronchial lesions. Although the patient was ANCA (antineutrophil cytoplasmic antibodies) negative, a differential diagnosis of granulomatosis with polyangiitis was established and confirmed pathologically. FDG PET/CT was useful for diagnosis of ANCA-negative granulomatosis with polyangiitis, in which tracheobronchial and cartilage lesions were prominent.